Analysis Of Uroliths (Urinary Stones) - VINODCHANDRAN; PRASANNACHANDRA M; UDAY NARAYAN SINGH; SREEKANTHA; YOGESH B; REMYA; VIVIAN D’SOUZA; BENEDICTA D’SOUZA (International Journal of Pharma and Bio Sciences, 2011)
Stone(s) or calculi in the urinary tract are referred as urolithiasis. Clinically they usually presents with acute abdominal pain, urinary obstruction and hematuria. In present study we have analyzed 50 patients with uroliths for the chemical composition to know their cause, complications and measures for the preventing the occurrence of urolithiasis. We found that 90% of uroliths found to be calcium related stones and 10% were uric acid stones. Metabolic dysregulation, diet and environmental factors have a causative role in the etiogenesis of urolithiasis.